Ján Rob Poničan (I am, I think, I feel, I love everything, but darkness I hate) - Michal Habaj (Slovenska Literatura, 2008)
The aim of the study is to determine typological coordinates of the debut written by Ján Rob Poničan and to follow realizations and transformations of semantic gesture in dependence on identity determined by style and literary movement, respectively on the basis of crossing different identities. Ján Poničan’s debut Som, myslím, cítim, milujem všetko, len temno nenávidím (I am, I feel, I love everything but darkness I hate, 1923) synthesizes poetics of several European Anvat-Gardes and modernistic movements. Eclectic character of the collection, and also two basic thematic cycles of the Poničans´s poetry - “fight“ and “love“ unite “revolutionary-romantic “ gesture determining aesthetic, noetic and ideological qualities in dependence on transformation of the typological ones. Influences of New-Romaticism, Decadence, Symbolism, Anarchism, Vitalism, Expressionism, Cubism and Futurism, Un-animism and proletarian poetry are many times realized in stylistically pure form, more often overlapping with significant tendency to connect, cross and combine different codes and poetics. Poničan´s debut seems aesthetically and ideologically quite destructed, but in terms of revolt also coherent expression as well as kaleidoscope of European culture from the end of 19th c. to the 20- ties of the 20th c. with many layers. Contribution of the study is mainly based on questioning the problem of the simplified conventional picture presenting Ján Poničan as a poet of proletarian ideology. Contrary to that it reveals variety and complicacy of typologically stylistic identity of Poničan´s debut.